Isolated Congenital Absence of Cranial Nerves: Report of Two Cases - Agarwal, Vivek; Vyas, Sameer; Dhawan, Sumeet R.; Sankhyan, Naveen (Neuropediatrics, 2018)
Isolated cranial nerve absence is a rare condition that can be diagnosed using high-resolution cranial nerve magnetic resonance (MR) imaging. Thorough clinical examination with proper knowledge of the course of cranial nerves may help diagnose this rare condition. We describe two cases, one each of, isolated congenital absence of the third and seventh cranial nerve with their clinical presentation. High-resolution T2-weighted MR imaging was done in both patients which revealed absence of cisternal segment of the right-sided third nerve and cisternal with canalicular segment of the right-sided facial nerve.
Keywords: isolated; cranial nerve; absence